2019
DOI: 10.1101/620633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isoform specificity of PKMs during long-term facilitation in Aplysia is mediated through stabilization by KIBRA

Abstract: Persistent activity of protein kinase M (PKM), the truncated form of protein kinase C (PKC), can maintain long-term changes in synaptic strength in many systems including the hermaphrodite marine mollusk, Aplysia californica. Moreover, different types of long-term facilitation (LTF) in cultured Aplysia sensorimotor synapses rely on the activities of different PKM isoforms in the presynaptic sensory neuron and postsynaptic motor neuron. When the atypical PKM isoform was required, the kidney and brain expressed … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…Thus, a shift in the balance of endosomal trafficking of AMPARs toward lysosomes can alter AMPAR proteostasis and availability of these channels for synaptic insertion. We find that KIBRA is required to maintain extrasynaptic pools of AMPARs in adult neurons, consistent with prior studies demonstrating that KIBRA can stabilize its binding partners against degradation (Xiao et al, 2011;Vogt-Eisele et al, 2014;Hu et al, 2017;Ferguson et al, 2019;Song et al, 2019). Interestingly, we also see a reduction in the KIBRA homolog WWC2 in adult KIBRA cKO neurons.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Thus, a shift in the balance of endosomal trafficking of AMPARs toward lysosomes can alter AMPAR proteostasis and availability of these channels for synaptic insertion. We find that KIBRA is required to maintain extrasynaptic pools of AMPARs in adult neurons, consistent with prior studies demonstrating that KIBRA can stabilize its binding partners against degradation (Xiao et al, 2011;Vogt-Eisele et al, 2014;Hu et al, 2017;Ferguson et al, 2019;Song et al, 2019). Interestingly, we also see a reduction in the KIBRA homolog WWC2 in adult KIBRA cKO neurons.…”
Section: Discussionsupporting
confidence: 91%
“…3A,B) supporting a role for KIBRA in AMPAR proteostasis. Consistent with prior work, we also observe a reduction in PKMζ (WT, 100 ± 2%; cKO 74 ± 2%, p < 0.001), a brain-specific kinase that interacts with KIBRA (Buther et al, 2004;Vogt-Eisele et al, 2014;Ferguson et al, 2019). Acute reduction of KIBRA also decreased the basal expression of KIBRA homolog and binding partner WWC2 (Fig.…”
Section: Acute Reduction Of Kibra In Adult Neurons Reduces Basal Expr...supporting
confidence: 91%
See 2 more Smart Citations
“…Initially, pNEX was constructed with the AK01a gene (shaker K + channel), and microinjected into Aplysia neurons, which demonstrated that the AK01a channel could modulate the firing of the injected neuron and regulate synaptic interactions [61]. Subsequent studies used pNEX to overexpress the target proteins and elucidated molecular mechanisms of synaptic plasticity [62][63][64][65][66][67][68]. Notably, small molecule neurotransmitter receptors (1ɑ metabotropic glutamate receptor [69]) and biogenic amine receptors (octopamine receptor) [64]), which are G-protein coupled receptors, were also expressed in Aplysia neurons through the vector pNEX.…”
Section: Introductionmentioning
confidence: 99%